2007
DOI: 10.1016/j.jamcollsurg.2007.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Resection in Veterans Affairs and Selected University Medical Centers: Results of the Patient Safety in Surgery Study

Abstract: Pancreatectomies are high-risk operations with substantial perioperative morbidity and mortality. Risk-adjusted outcomes for patients treated at PS hospitals were found to be superior to those for patients treated at VA hospitals in the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
44
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 24 publications
1
44
1
Order By: Relevance
“…[40][41][42][43][44] In a study comparing quality of care in nursing homes, veterans in VA nursing homes were less likely to develop a pressure ulcer than veterans in community nursing homes. 31 However, other studies found that morbidity among VA patients is worse after pancreatectomy 28 and for male patients only after gastric bypass, compared to patients in private sector hospitals (unadjusted). 41 Complications.…”
Section: Safetymentioning
confidence: 97%
See 1 more Smart Citation
“…[40][41][42][43][44] In a study comparing quality of care in nursing homes, veterans in VA nursing homes were less likely to develop a pressure ulcer than veterans in community nursing homes. 31 However, other studies found that morbidity among VA patients is worse after pancreatectomy 28 and for male patients only after gastric bypass, compared to patients in private sector hospitals (unadjusted). 41 Complications.…”
Section: Safetymentioning
confidence: 97%
“…17 However, some studies found higher surgical mortality among VA patients compared with non-veterans. 19,22,[26][27][28][29] Lower mortality rates were observed after cataract surgeries for VA patients compared with veterans who are Medicare fee-forservice beneficiaries. 30 Mortality among veterans residing in VA nursing homes and community nursing homes was similar.…”
Section: Safetymentioning
confidence: 99%
“…Postoperative morbidity was lower for VA patients compared with non-Veterans receiving non-VA care Hutter et al, 2007;Johnson et al, 2007). In several studies, morbidity after several types of surgery did not differ between VA patients and nonVeterans receiving non-VA care (Hall et al, 2007;Lancaster et al, 2007;Lautz et al, 2007;Neumayer et al, 2007;Turrentine et al, 2007), but was worse for VA patients overall (Glasgow et al, 2007) and male VA patients (Lautz et al, 2007). In studies comparing quality of care for Veterans receiving VA care and non-VA care, Veterans residing in VA nursing homes were less likely to develop a pressure ulcer than Veterans in community nursing homes (Berlowitz et al, 2005).…”
Section: Safety Of Care In Va Compared With Non-vamentioning
confidence: 95%
“…Adjusted mortality was lower among Veterans who used VA care compared with male Medicare Advantage beneficiaries over 65 years of age (Selim, Berlowitz, et al, 2010;Selim, Kazis, Qian, et al, 2009;Selim et al, 2006;Selim et al, 2007). Mortality after some surgeries was higher among VA patients compared with non-Veterans receiving non-VA care (Campling et al, 2005;Chakkera et al, 2004;Glasgow et al, 2007;Henderson et al, 2007;Vaughan-Sarrazin, Wakefield, & Rosenthal, 2007) and after other surgeries, similar (Vaughan-Sarrazin, Wakefield, & Rosenthal, 2007). Mortality within one year of admission after hip fracture was 21 per cent lower among Veterans admitted to non-VA hospitals compared with Veterans admitted to VA hospitals (Richardson et al, 2013).…”
Section: Safety Of Care In Va Compared With Non-vamentioning
confidence: 99%
“…However, pancreaticoduodenectomy (PD) remains associated with a substantial and well-documented morbidity (29-52%) [1][2][3][4] and mortality (1-4%) in experienced centres. 5,6 A total of 144 consecutive PD resections were performed in our institution by four surgeons.…”
mentioning
confidence: 99%